An Analysis of Vladimir Propp's Narrative Functions on The Northman Movie - Alief Bagastiaji Suwarno; Suparto Suparto (JEdu: Journal of English Education, 2023)
This research discusses the narrative functions and sphere of actions that appear in The Northman movie using Vladimir Propp’s theory.  The objectives of this research are to identify and analyze the narrative functions and Proppian archetypes, then find out how many of them contain in The Northman movie. The writer uses a descriptive qualitative method to analyze the obtained data. The results show that there are 19 out of 31 narrative functions and 5 out of 7 Proppian archetypes found in The Northman movie. The narrative functions found in the movie are Absentation, Reconnaissance, Delivery, Trickery, Villainy, Mediation, Beginning of Counteraction, Departure, First Function of The Donor, The Hero’s Reaction, Receipt of a Magical Agent, Guidance, Struggle, Victory, Pursuit, Rescue, Difficult Task, Solution, and Exposure. The Proppian archetypes in the movie are Hero, Villain, Donor, Helper, and Dispatcher. This research shows that the theory can be applied in analyzing Old-Norse-influenced epic, and several characters in a story have a specific function that drives the stages in a narrative.